Prokaryotic Capability to Use Organic Substrates Across the Global Tropical and Subtropical Ocean - Sala, Maria Montserrat; Ruiz-González, Clara; Borrull, Encarna; Azúa, Iñigo; Baña, Zuriñe; Ayo, Begoña; Álvarez-Salgado, X. Antón; Gasol, Josep M.; Duarte, Carlos M. (Frontiers in Microbiology, 2020)
Prokaryotes play a fundamental role in decomposing organic matter in the ocean but little is known about how microbial metabolic capacities vary at the global ocean scale and what are the drivers causing this variation. We aimed at obtaining the first global exploration of the functional capacities of prokaryotes in the ocean, with emphasis on the under-sampled meso- and bathypelagic layers. We explored the potential utilization of 95 carbon sources with Biolog GN2 plates® in 441 prokaryotic communities sampled from surface to bathypelagic waters (down to 4000 m) at 111 stations distributed across the tropical and subtropical Atlantic, Indian and Pacific oceans. The resulting metabolic profiles were compared with biological and physico-chemical properties such as FDOM or temperature. The relative use of the individual substrates were remarkably consistent across oceanic regions and layers, and only the Equatorial Pacific Ocean showed a different metabolic structure. When grouping substrates by categories, we observed some vertical variations, such as an increased relative utilization of polymers in bathypelagic layers, or a higher relative use of P-compounds or amino acids in the surface ocean. The increased relative use of polymers with depth, together with the increases in humic-DOM suggest that deep ocean communities have the capability to process complex DOM. Overall, the main identified driver of the metabolic structure of ocean prokaryotic communities was temperature. Our results represent the first global depiction of the potential use of a variety of carbon sources by prokaryotic communities across the tropical and subtropical ocean and show that acetic acid clearly emerges as one of the most widely potentially used carbon sources in the ocean.